THE CONCEPT OF GENDER JUSTICE IN SURAH AL-BAQARAH/2:234 REGARDING THE LAW OF ʿIDDAH - ASM, U. Saifuddin; Nur'aeni, Ulvah (Takafu: Journal of Tafsir and Gender Perspective, 2025)
Surah Al-Baqarah verse 234 is one of the important verses that regulates ‘iddah—the waiting period for a woman whose husband has passed away, lasting four months and ten days. Normatively, this verse is often understood as an obligation for women to preserve their dignity and ensure the certainty of lineage. However, from a gender perspective, this verse carries a deeper meaning related to the position and protection of women within the Islamic social system. This study aims to analyze the meaning of justice and protection for women in the provision of ‘iddah as stated in QS. Al-Baqarah verse 234, using a thematic (maudhu‘i) and gender hermeneutic approach. The research employs a qualitative method based on a literature study and applies the TA9-based exegesis methodology (Tamhid, Tartib al-Ayat, Tarikh, Tanasub al-Ayat with other verses, Tanasub al-Ayat with Hadith, Tarjamah Mufradat, Tahlil Tafsir, Takwil al-Ayat, and Tathbiq). The findings show that the provision of ‘iddah is not a form of women’s subordination, but rather an expression of respect for their dignity and rights. From the Qur’anic perspective, this rule serves as a social and psychological transition period for women to gain inner peace, legal protection, and space to reorganize their lives after the loss of a spouse. Thus, QS. Al-Baqarah verse 234 reflects a balanced value of gender justice, where the Qur’an places women as legal subjects who have the right to make life choices after the completion of the ‘iddah period. These findings affirm that Islamic teachings, when understood contextually, support the principles of justice, well-being, and respect for women as beings equal before Allah.